HPLC and Chemical Methods for The Determination of Vitamin B-Complex in Rice and Rice Products - Raghav, S.S.; Chakraborti, I.; Sarin, R.K.; P. Tyagi, Bijender; P. Sharma, Gyan; Tyagi, V.P. (Asian Journal of Chemistry, 2010)
Evaluation of high performance liquid chromatography (HPLC) and chemical methods for vitamin B-complex, namely, thiamine, riboflavin and niacin in rice and rice products was carried out. No significant difference in the accuracy of results was observed between two methods of determination for thiamine and riboflavin. But there is significant difference in case of niacin. The study undertaken may find application for the correction and standardization of analysis method for B-vitamins.